2021
DOI: 10.1093/neuonc/noab196.535
|View full text |Cite
|
Sign up to set email alerts
|

Nimg-35. Machine Learning Glioma Grade Prediction Literature: A Tripod Analysis of Reporting Quality

Abstract: PURPOSE Reporting guidelines are crucial in model development studies to ensure the quality, transparency and objectivity of reporting. While machine learning (ML) models have proven themselves effective in predicting glioma grade, their potential use can only be determined if they are clearly and comprehensively reported. Reporting quality has not yet been evaluated for ML glioma grade prediction studies, to our knowledge. We measured published literature against the TRIPOD Statement, a chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Both studies found very similar TRIPOD adherence indices (44% and 48%) as well as similar deficiencies in the individual items. 55,56 Our results suggest that deficiencies in transparent reporting are a broader issue in the field of neuro-oncologic imaging.…”
Section: Discussionmentioning
confidence: 80%
“…Both studies found very similar TRIPOD adherence indices (44% and 48%) as well as similar deficiencies in the individual items. 55,56 Our results suggest that deficiencies in transparent reporting are a broader issue in the field of neuro-oncologic imaging.…”
Section: Discussionmentioning
confidence: 80%